P040 Reduced serological response to COVID-19 vaccines in patients with IBD is further diminished by TNF inhibitor therapy; Early results of the VARIATION study (VAriability in Response in IBD Against SARS-COV-2 ImmunisatiON). (21st January 2022) - Doherty, J; Stack, R; O' Morain, N; Girod, P; Tosetto, M; Inzitari, R; Sheridan, J; Cullen, G; Buckley, M; Mulcahy, H; Ryan, E J; Daghfal, D; et al.
Abstract: Background: Patients with inflammatory bowel disease (IBD) have attenuated responses to current vaccinations. There is a limited body of evidence suggesting patients with IBD receiving TNF antagonists have an attenuated response to vaccination against COVID-19. We sought to determine the impact of IBD and various medications for the treatment of IBD on antibody responses to vaccination against COVID-19. Methods: Patients with IBD (n=270) and healthy controls (HC, n=116) were recruited prospectively and quantitative antibody responses were assessed following 1 st and 2 nd doses of COVID-19 vaccination. The impact of IBD and medications for treatment of IBD on vaccine response rates was investigated. Results: All HC seroconverted post complete vaccination [100%]. A small proportion of patients with IBD failed to seroconvert [2%]. Median IgG spike protein (SP) antibody levels post-complete vaccination in our IBD cohort was significantly lower than HC [2, 613 AU/mL versus 6, 871 AU/mL, p=<0.001]. A diagnosis of IBD and viral-vector vaccine use were independently associated with lower IgG SP antibody levels. Patients with IBD receiving anti-TNF therapy had significantly lower IgG SP antibody levels [2444.6 AU/mL] than IBD patients not receiving these agents [3867.6 AU/mL]. Patients with IBD not receiving TNF inhibitors still showed attenuated responses compared to HC receiving a similar vaccine [p = < 0.001].[Figure 1]. IgG SP antibody levels in our IBD cohort reduced rapidly during follow up. Conclusion: Patients with IBD who do not seroconvert post-vaccination against COVID-19 are a vulnerable cohort. Patient with IBD have attenuated serological responses to SARS-CoV-2 vaccination. Use of anti-TNF therapy further impacts IgG SP antibody levels. Impaired response to vaccination in our study highlights the importance of booster vaccination programmes for patients with IBD.